Numerical Study of Shear Stress Distribution Over Sand Ripples Under Terrestrial and Martian Conditions. Issue 1 (28th January 2019) - Siminovich, A.; Elperin, T.; Katra, I.; Kok, J. F.; Sullivan, R.; Silvestro, S.; Yizhaq, H.
Abstract: Ripples occur on Earth and Mars in a range of sizes. From terrestrial studies, ripple size is known to depend on grain‐size frequency, wind duration, wind strength (including stronger winds that can flatten ripples), and fundamental environmental factors that differ between the two planets. Here we use computational fluid dynamics (CFD) experiments to model boundary layer shear stresses applied to aeolian ripple surfaces, to investigate how these stresses might differ between Earth and Mars. CFD experiments used ANSYS Fluent, with inlet wind speeds of 10 and 15 m/s for both planetary environments. Ripple profiles for Earth and Mars were developed using saltation and reptation properties modeled by the numerical saltation model COMSALT (Kok & Renno, 2009, https://doi.org.10.1029/2009JDO11702 ) to develop ripple profiles using the numerical technique of Yizhaq et al. (2004, https://doi.org.10.1016/j.physd.2004.03.015 ). Although the CFD experiments using these inputs could not include the effects of a saltation cloud, results are robust enough to indicate clearly that for similar modeled wind speeds on Earth and Mars, boundary layer shear stress applied to ripple surfaces is greater on Earth under conditions for which sand transport is expected. These results indicate that ripples can grow larger on Mars than on Earth, because for typical Martian wind speeds the shear velocity at the ripple crests is below the fluid threshold. Plain Language Summary: Elucidating the origin of many natural patterns on Earth and planetary surfaces is a challenging problem of pattern formation in complex systems. Among these mysterious phenomena are the aeolian sand ripples, which are a common pattern of granular matter on Earth and on Mars. Ripple wavelength on Earth is <30 cm, and height is less than 1 cm, whereas on Mars they might be much larger both in wavelength and height. On Mars, two sizes of aeolian ripples were observed, small (decimeter scale) impact ripples like those on Earth and large, meter‐scale ripples with no terrestrial analog. The large ripples on Mars were detected in orbital images and first visited in situ by the NASA Mars Exploration Rover Spirit at the El Dorado ripple field in Gusev Crater. The existence of very large ripples on Mars lacking exact terrestrial analogues is not fully understood at this time and is still a matter of conjecture and debate. In this study, computational fluid dynamics simulations over simulated sand ripples illustrate the differences in shear stress expected at ripple crests on Earth and Mars under two test flow wind speeds. The distribution of the shear stress over ripple crest is important for predicting the entrainment from the crest, which is one of several possible mechanisms for limiting ripple growth by removing grains from the crest, yet its relative importance on Earth and Mars is not understood. The Martian ripple profile was three times larger in the experiments than the terrestrial ripple profile but still several factors smaller than the largest ripples encountered by Mars rovers. Despite this, shear velocities along Martian ripple crests did not reach the critical velocity where erosion from the crest occurs, while at the crests of the smaller terrestrial ripples, the critical velocity was exceeded at the same test inlet wind speeds. These results indicate that fluid shear stress is a more important factor for controlling ripple size on Earth than on Mars and may help to explain why impact ripples on Mars can grow larger than on Earth. These results are useful for understanding the aeolian processes involved in ripple formation under Martian atmospheric conditions. Further studies are needed to verify this conclusion for more realistic larger Martian ripples and for higher shear velocities. Key Points: Computational fluid dynamics experiments to model boundary layer shear stresses were applied to aeolian ripples under Earth and Mars conditions Shear velocities along Martian ripples did not reach fluid threshold, while at the crests of smaller terrestrial ripples, it was exceeded Fluid shear stress is a more important factor for controlling ripples size on Earth than on Mars